(untitled) (World of finance, 2024)
Introduction. The concept of sustainable development, which has been recognized by the UN and all countries of the world over the past 30-40 years, has become the consensus official paradigm of the world economy in the 21st century. The changed paradigm of the global economy, the foundation of which became the "Goals of sustainable development, the climate agenda and ESG – the transition created a new mega trend of the financial industry – “sustainable finance or finance of new quality”. “Green finance” is considered as a strategic direction of sustainable financing. The purpose of the article is to substantiate theoretical and practical conceptual approaches to the definitions of “green economy” and “green finance” in the new paradigm of the global economy, as well as their use in the sustainable investment development of Ukrainian economy. Results. Key initiatives in the field of sustainable development, as well as conceptual approaches to the definitions of "green economy" and "green finance" are considered. Focused attention on the concept of sustainable finance, the trend of which foresees a revolutionary approach from the classical paradigm of finance to a new paradigm. Financing instruments and mechanisms, such as green bonds, credits and loans, which are not fundamentally new in technical terms, but contain an ecological component, have been analyzed. It is argued that the concept of sustainable development finance acquires both theoretical justification and practical confirmation in the academic discourse. The NBU strategic approaches to the construction and development of sustainable financing, taking into account ESG factors in the European integration vector of Ukraine were studied. Conclusions. It is justified that the paradigm of sustainable finance should be considered in an inextricable relationship with the notions of sustainable development and sustainable investment, which is correlated with the achievement of sustainable development goals. In further scientific research, it is necessary to pay special attention to the key principles of the development of sustainable financing in Ukraine, especially the implementation of environmental, social and managerial (ESG) factors, which will become mandatory elements of the corporate management systems of financial institutions.